Bezpośredni zakaz reformationis in peius a rozstrzygnięcia sądu odwoławczego w przedmiocie kosztów procesu - Markiewicz, Tymon (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The article concerns the relation of the reformationis in peius prohibition and the decisions of the appellate court regarding the costs of proceedings, in particular the fee from Article 8 of the Act on Fees in Criminal Proceedings. The author analyses the institution stated in Article 426 § 2 and Article 434 of the Polish Code of Criminal Procedure (k.p.k.), taking the position that the prohibition stated in Article 434 k.p.k. applies to decisions regarding the costs of proceedings. Particular consideration was given to Article 8 of the Act on Fees in Criminal Proceedings. The author states that this provision is contrary to the idea of reformationis in peius prohibition and seems to be inconsistent with the constitutional model of the right to appeal and the principle of two-instance proceedings.